2021
DOI: 10.1016/j.actamat.2020.116595
|View full text |Cite
|
Sign up to set email alerts
|

Segregation and precipitation stabilizing an ultrafine lamellar-structured Al-0.3%Cu alloy

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…During migration of the Y-junction shown in figure 4, an externally attached interconnecting boundary on the left-hand side interacted with the Y-junction, retarding its migration. Such a pinning effect was also found for attached lamellar boundaries, particles, and dislocations [29,36]. The geometry of a Y-junction is important in determining its stability, in particular the spacing D and the dihedral angle 2θ associated with the migrating lamella.…”
Section: Uniform Coarsening By Y-junction Motionmentioning
confidence: 76%
“…During migration of the Y-junction shown in figure 4, an externally attached interconnecting boundary on the left-hand side interacted with the Y-junction, retarding its migration. Such a pinning effect was also found for attached lamellar boundaries, particles, and dislocations [29,36]. The geometry of a Y-junction is important in determining its stability, in particular the spacing D and the dihedral angle 2θ associated with the migrating lamella.…”
Section: Uniform Coarsening By Y-junction Motionmentioning
confidence: 76%
“…Compared with the solution treated sample [9], finer lamellae are observed in regions deeper from the surface, which indicates that the precipitation introduced by aging treatment before deformation can effectively inhibit dynamic recovery of the alloy during deformation. Shuai et al [17] observed the pinning phenomenon of Al 2 Cu particles to triple junctions in Al-0.3wt.%Cu by insitu electron microscopy, indicating that the second phase particles can improve the stability of the alloy. This stabilization mechanism also plays an important role in the deformation process of the samples in the aging state.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the low diffusion capability at low deformation temperature, these atoms still remain around the decomposed precipitates. Segregation and precipitation in the peak-aged sample can stabilize the grain boundaries from both a thermodynamic and kinetic perspective, and restrain dynamic recovery in the deformation process [17], which leads to thinner lamellar spacing compared with solute-treated SSFT samples [9]. APT can provide abundant 3D chemical information but limited crystallographic knowledge, while 3D-OMiTEM is an effective complementary technique.…”
Section: D-omitem Observationsmentioning
confidence: 99%
“…However, the effects of TJs on strength were largely overlooked. Some researchers have also noticed the connection between TJs and dislocation nucleation [11,12] and GB activities, [13,14] which are essential factors in determining the strength of polycrystalline materials. By in situ compression of coarse-grained and nano-grained nanoporous gold samples in an electrochemical environment, [8] the effect of surface triple junction (STJ) on the strength of nanoporous gold was successfully decoupled from the GB and surface effects.…”
Section: Introductionmentioning
confidence: 99%
“…And for the annealing recrystallization process of layered polycrystalline aluminum or nickel in the cold rolled state, the dominant role of Y‐junctions in the process of GB coordination deformation is demonstrated. [ 13–15 ] Moreover, atomic‐scale simulations [ 16 ] also proved that the drag obstruction of TJs on adjacent GBs is more pronounced at small sizes, low Σ GBs, or low temperatures. This effect affects the dihedral angle size of TJs, which in turn further affects the migration of TJs.…”
Section: Introductionmentioning
confidence: 99%